Propagation of short, nonlinear, second-sound pulses through He-II in one- and three-dimensional geometry - Efimov, V. B.; Kolmakov, G. V.; Kuliev, A. S.; Mezhov-Deglin, L. P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The results of an experimental study of the evolution of the shape of nonlinear second-sound pulses in superfluid He-II are reported. The pulses propagate in the bulk (3D geometry) and along a cryoacoustic waveguide filled with liquid helium (quasi-1D geometry) at temperatures corresponding to the negative, positive, or zero nonlinearity coefficient. A strong dependence of the shape of the propagating pulse on the dimensionality of the wave was observed. The finite size of the heater (generator of a sound) affects the profile of a short 3D pulse even at distances many times greater than the heater size, which restricts the minimal width of the excited pulse. The experimental data are compared with the results of numerical simulations.